The Effect Of Academic Supervision And Transformational Leadership On Madrasah Principals' Competence Of Educators - Aji Wahyudin; Muhammad Afif Choironi; Febriyan Kurniawan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This study aims to find out how effective is the implementation of academic supervision, the application of transformational leadership of madrasa principals and educator competencies, and to find out how much influence academic supervision has on educator competence, and determine the effect of transformational leadership on educator competence, and also to find out the influence of academic supervision and transformational leadership together on the competence of educators at MTs Negeri 6 Kediri. This study aims to determine and analyze the effectiveness of the implementation of academic supervision of transformational leadership of school principals, and the competence of teaching staff, and to analyze the effect of academic supervision and transformational leadership on the competence of teaching staff at MTs Negeri 6 Kediri partially or simultaneously. This study used quantitative methods with a population of 65 and a sample of 53 respondents and data collection techniques using a questionnaire. The results of the study show that (1) The effectiveness of academic supervision at MTs Negeri 6 Kediri is in the high and very high categories. (2) The effectiveness of the principal's transformational leadership applied at MTs Negeri 6 Kediri belongs to the high and very high categories. (3) Educator Competency Effectiveness of MTs Negeri 6 Kediri in the High and Very High Categories. (4) There is a significant influence between academic supervision on the competence of teaching staff at MTs Negeri 6 Kediri with a percentage of 8%. (2) There is a significant influence between the principal's transformational leadership on the competence of the teaching staff at MTs Negeri 6 Kediri with a percentage of 42.3%, (33) There is a significant influence between academic supervision and the transformational leadership of the madrasa principal together on the competence of the staff teachers at MTs Negeri 6 Kediri percentage of 42.3%. And the rest is influenced by other factors that are not discussed in this study.